The ability to bounce beyond : the contribution of the school environment to the resilence of Dutch urban middle-adolescents from a low socio-economic background - Bouwer, A.C., 1946- (University of Pretoria, 2013)
Thesis (PhD (Learning Supoort, Guidance and Counselling))--University of Pretoria, 2007.